2018
DOI: 10.1002/biot.201700706
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Optimization Reduces Phosphorylation and Hydroxylation Level on an Fc-Fusion Protein in a CHO Fed-Batch Process

Abstract: Phosphorylation and hydroxylation are post translational modifications (PTMs) rarely observed or reported in biopharmaceuticals. While developing a stable CHO cell line and a fed-batch process to produce a biosimilar dulaglutide, a GLP1-Fc fusion protein, the authors identified both serine phosphorylation and lysine hydroxylation. While the innovator dulaglutide contains less than 2% phosphorylated and only ≈6.5% hydroxylated GLP1-Fc molecules, the clones that the authors obtained in the platform fed-batch pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Gangwar et al also indicated that vitamins can inhibit the acidic variants while it enhances the basic variants (Gangwar et al 2021 ). Hou et al found that increasing rate of vitamin C and nicotinamide feeding can reduce the phosphorylation level in CHO cells to 3% and attenuated the hydroxylation level to 9.4% (Hou et al 2019 ). Adding B vitamins including 0.005 g/L vitamin B2, 0.0035 g/L pyridoxine (vitamin B6), 0.03 g/L pyridoxal (vitamin B6), 0.0985 g/L folic acid and 0.024 g/L vitamin B12 can improve packed cell volume (PCV) and antibody titer (Vijayasankaran et al 2013 ).…”
Section: Vitaminmentioning
confidence: 99%
“…Gangwar et al also indicated that vitamins can inhibit the acidic variants while it enhances the basic variants (Gangwar et al 2021 ). Hou et al found that increasing rate of vitamin C and nicotinamide feeding can reduce the phosphorylation level in CHO cells to 3% and attenuated the hydroxylation level to 9.4% (Hou et al 2019 ). Adding B vitamins including 0.005 g/L vitamin B2, 0.0035 g/L pyridoxine (vitamin B6), 0.03 g/L pyridoxal (vitamin B6), 0.0985 g/L folic acid and 0.024 g/L vitamin B12 can improve packed cell volume (PCV) and antibody titer (Vijayasankaran et al 2013 ).…”
Section: Vitaminmentioning
confidence: 99%
“…7 Together, these observations and the data presented here demonstrate that CHO cells are generally capable of introducing high levels of hydroxyproline and sulfotyrosine in therapeutic proteins, which thereby significantly increase the heterogeneity of the molecules. In a very recent study by Hou et al, 12 the impact of specific nutrients on phosphoserine (~20%) and hydroxylysine (~25%) of a CHO platform, fed batch-produced Fc-fusion protein was reported. Although the exact influence of the nutrients is unknown, increased vitamin C, ferric citrate, and niacinamide feeding rates and a decreased cysteine feeding rate reduced the phosphorylation level to~3%.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Further uncommon enzyme-catalyzed PTMs (based on the experience and knowledge from IgGs and monoclonal antibodies (mAbs)) have been reported in non-IgG domains and linkers of antibody-fusion proteins. [8][9][10][11][12] In therapeutic proteins, PTMs are especially critical if they negatively influence drug potency or drug safety. Even if PTMs just increase the product heterogeneity of the desired molecules, when identified they need to be diminished or removed by manufacturing process optimizations or further protein engineering, or they at least have to be monitored and controlled to demonstrate batch consistency or comparability of manufactured clinical material.…”
Section: Introductionmentioning
confidence: 99%
“…The density and viability of cells were determined before each feeding. Supernatant harvest and antibody purification followed procedures described previously (54).…”
Section: Methodsmentioning
confidence: 99%